Clima Laboral en el comercial Pio Lindo del cantón Babahoyo. - Conforme Méndez, Johnny Washington (2022)
The present case study is about the work environment of the commercial Pio Lindo, the objective is to analyze the work environment maintained by the commercial and the perception of its collaborators, about its activities that are developed within it and its functional trajectory of the type of work performed by each of the employees of the organization, the negative effects of maintaining a conflictive work environment, work stress, lack of leadership, communication, when solving the internal problems of the company. This case deals with the perception that the collaborators have of the internal environment of the company, and their personal behavior regarding the fundamental parts that must form a good working environment in the Pio Lindo commercial, which due to carelessness of the highest authority is not organized and that in turn determine the shortcomings that are observed by the employees of this organization, using support to obtain information, a descriptive and explanatory methodology is used that allows an analysis of the current situation of the commercial object of study. According to the results obtained from the analysis of the surveys, the same one that included the participation of all the collaborators and the manager of the commercial, a level of dissatisfaction is noted on the part of the workers, who do not have adequate communication. By their leader, causing joint decisions not to be made when a conflict occurs, generating tension and stress in them by having an additional burden to solve, by not receiving a positive response from their leader, they become discouraged and do not give their better job performance.